Evolutionary conservation pattern of zinc-finger domains of Drosophila segmentation genes. - Sommer, R J (1992)
A number of genes of the developmental gene hierarchy in Drosophila encode transcription factors containing Cys2His2 zinc finger domains as DNA-binding motifs. To learn more about the evolution of these genes, it is necessary to clone the homologs, or more correctly the orthologs, from different species. Using PCR, we were able to obtain apparently orthologous fragments of hunchback (hb), Krüppel (Kr), and snail (sna) from a variety of arthropods and partly also from other animal phyla. Sequence alignments of these fragments show that the amino acid differences can normally not be correlated with the evolutionary distances of the respective species. This is due to an apparent saturation of potential replacements within the finger domains, which is also evident from the frequent occurrence of convergent replacements. Another recurrent feature of these alignments is that those amino acids that are directly involved in determining the DNA-binding specificity of the fingers are most conserved. Using in vitro bandshift experiments we can indeed show that the binding specificity of a hunchback finger fragment from different species is not changed. This implies that there is a high selective pressure to maintain the regulatory target elements of these genes during evolution.